Potential Protective Role Exerted by Secoiridoids from Olea europaea L. in Cancer, Cardiovascular, Neurodegenerative, Aging-Related, and Immunoinflammatory Diseases - María Luisa Castejón; Tatiana Montoya; Catalina Alarcón-; Marina Sánchez-Hidalgo (MDPI AG, 2020)
Iridoids, which have beneficial health properties, include a wide group of cyclopentane [c] pyran monoterpenoids present in plants and insects. The cleavage of the cyclopentane ring leads to secoiridoids. Mainly, secoiridoids have shown a variety of pharmacological effects including anti-diabetic, antioxidant, anti-inflammatory, immunosuppressive, neuroprotective, anti-cancer, and anti-obesity, which increase the interest of studying these types of bioactive compounds in depth. Secoiridoids are thoroughly distributed in several families of plants such as Oleaceae, Valerianaceae, Gentianaceae and Pedialaceae, among others. Specifically, Olea europaea L. (Oleaceae) is rich in oleuropein (OL), dimethyl-OL, and ligstroside secoiridoids, and their hydrolysis derivatives are mostly OL-aglycone, oleocanthal (OLE), oleacein (OLA), elenolate, oleoside-11-methyl ester, elenoic acid, hydroxytyrosol (HTy), and tyrosol (Ty). These compounds have proved their efficacy in the management of diabetes, cardiovascular and neurodegenerative disorders, cancer, and viral and microbial infections. Particularly, the antioxidant, anti-inflammatory, and immunomodulatory properties of secoiridoids from the olive tree (Olea europaea L. (Oleaceae)) have been suggested as a potential application in a large number of inflammatory and reactive oxygen species (ROS)-mediated diseases. Thus, the purpose of this review is to summarize recent advances in the protective role of secoiridoids derived from the olive tree (preclinical studies and clinical trials) in diseases with an important pathogenic contribution of oxidative and peroxidative stress and damage, focusing on their plausible mechanisms of the action involved.